The Effect of Hidden Curriculum on the Behavior of Students in Physical Education - Parvin Samadi; Roqyye Heydari (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The present study aimed at evaluating the impact of hidden curriculum on the behavior of students of physical education and high school students in Tehran. Due to the nature of the subject, the research method was descriptive-analytical. The statistical population of the study was secondary school students of Tehran and the number of students was 200 male and female students of career schools, and 188 students from different secondary schools were selected with Cochrane method which is a multilevel cluster randomized sampling. In this research, data collection was accomplished through researcher-made questionnaire. On this basis, to determine the amount of the impact of hidden curriculum on the research categories, an interview was used. In this research, the validity of the questionnaire was confirmed by the professors and experts and its reliability was 0.95 which was obtained by the use of Cronbach Alpha for the hidden curriculum. The results showed that the effects of the hidden curriculum of the study (rules, regulations, social relationship, physical environment, human resources, cultural and educational, sports equipment and materials) on the behaviors of students was significantly much. Besides, there is a difference between hidden curriculum (in the dimensions of environment and physical space, human researches, and cultural, educational and sports materials and equipment) and gender-based behavior.